Prevalence of Skin Cancer in Chronic Arsenicosis in Chittagong Medical College Hospital - Alam, Mansurul; Hazari, Saroj Kanti Singh; Alam, ASM Tawhidul (Journal of Chittagong Medical College Teachers' Association, 2011)
Key words: chronic arsenicosis, prevalence; skin cancer DOI: 10.3329/jcmcta.v21i1.7666 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):23-29